Rapid assessments accurately identify threatened Australian flora under IUCN Red List Criteria after megafires - Tom Le Breton; Mark K.J. Ooi; Sylvia Hay; Joe Atkinson; Doug Bickerton; Stephanie Cerato; Richard J.P. Davies; Chantelle Doyle; Rachael Gallagher; Bettina Ignacio; David Keith; Mellissa McCallum; et al. (Biological Conservation, 2025)

Mechanistic safety assessment via multi-omic characterisation of systemic pathway perturbations following in vivo MAT2A inhibition - Valentina Fogal; Filippos Michopoulos; Andrew F. Jarnuczak; Ghaith M. Hamza; Stephanie Harlfinger; Paul Davey; Heather Hulme; Stephen J. Atkinson; Piotr Gabrowski; Tony Cheung; Michael Grondine; Clare Hoover; et al. (Archives of Toxicology, 2024)
The tumour suppressor p16/CDKN2A and the metabolic gene, methyl-thio-adenosine phosphorylase (MTAP), are frequently co-deleted in some of the most aggressive and currently untreatable cancers. Cells with MTAP deletion are vulnerable to inhibition of the metabolic enzyme, methionine-adenosyl transferase 2A (MAT2A), and the protein arginine methyl transferase (PRMT5). This synthetic lethality has paved the way for the rapid development of drugs targeting the MAT2A/PRMT5 axis. MAT2A and its liver- and pancreas-specific isoform, MAT1A, generate the universal methyl donor S-adenosylmethionine (SAM) from ATP and methionine. Given the pleiotropic role SAM plays in methylation of diverse substrates, characterising the extent of SAM depletion and downstream perturbations following MAT2A/MAT1A inhibition (MATi) is critical for safety assessment. We have assessed in vivo target engagement and the resultant systemic phenotype using multi-omic tools to characterise response to a MAT2A inhibitor (AZ’9567). We observed significant SAM depletion and extensive methionine accumulation in the plasma, liver, brain and heart of treated rats, providing the first assessment of both global SAM depletion and evidence of hepatic MAT1A target engagement. An integrative analysis of multi-omic data from liver tissue identified broad perturbations in pathways covering one-carbon metabolism, trans-sulfuration and lipid metabolism. We infer that these pathway-wide perturbations represent adaptive responses to SAM depletion and confer a risk of oxidative stress, hepatic steatosis and an associated disturbance in plasma and cellular lipid homeostasis. The alterations also explain the dramatic increase in plasma and tissue methionine, which could be used as a safety and PD biomarker going forward to the clinic.

Informed Decision-Making and Satisfaction with a Church-Based Men’s Health Workshop Series for African-American Men: Men-Only vs. Mixed-Gender Format - Cheryl L. Holt; Daisy Le; Darlene R. Saunders; Min Qi Wang; Jimmie L. Slade; Bettye Muwwakkil; Ralph Williams; Nancy L. Atkinson; Tony L. Whitehead; Michael Naslund (Journal of Cancer Education, 2015)

Erratum to: The association of active smoking with multiple cancers: national census-cancer registry cohorts with quantitative bias analysis - Tony Blakely; Jan J. Barendregt; Rachel H. Foster; Sarah Hill; June Atkinson; Diana Sarfati; Richard Edwards (Cancer Causes & Control, 2014)

The association of active smoking with multiple cancers: national census-cancer registry cohorts with quantitative bias analysis - Tony Blakely; Jan J. Barendregt; Rachel H. Foster; Sarah Hill; June Atkinson; Diana Sarfati; Richard Edwards (Cancer Causes & Control, 2013)

High rates of endometrial cancer among Pacific women in New Zealand: the role of diabetes, physical inactivity, and obesity - Ineke Meredith; Diana Sarfati; Takayoshi Ikeda; June Atkinson; Tony Blakely (Cancer Causes & Control, 2012)

Social inequalities or inequities in cancer incidence? Repeated census-cancer cohort studies, New Zealand 1981–1986 to 2001–2004 - Tony Blakely; Caroline Shaw; June Atkinson; Ruth Cunningham; Diana Sarfati (Cancer Causes & Control, 2011)

Patterns of Disparity: Ethnic and Socio-economic Trends in Breast Cancer Mortality in New Zealand - Diana Sarfati; Tony Blakely; Caroline Shaw; Donna Cormack; June Atkinson (Cancer Causes & Control, 2006)

A microbiological survey of Montserrat Island hydrothermal biotopes - Tony Atkinson; Steven Cairns; D. A. Cowan; Michael J. Danson; David W. Hough; D. Barrie Johnson; Paul R. Norris; Neil Raven; Clare Robinson; Rob Robson; Richard J. Sharp (Extremophiles, 2000)